Vous êtes sur la page 1sur 9

x

x 2 x 1 = 0

f (x) sin(x)

x

x

f (n) = n 3 +3n 2 2n

3n 3 1

f (x) g(x) x f (1)

g

´

3 3x 3 +sin(x) dx

1

x

1 n

2

x 3 − cos(x) + 1

250 200 150 100 50 0 −50 −100 −150 −200 −250 −6 −4 −2 0
250
200
150
100
50
0
−50
−100
−150
−200
−250
−6
−4
−2
0
2
4
6
x

f(x) = x 4 x 2

x

x R 4 x 2 0 4 x 2 = 0

4 x 2 [2, 2] D(f ) = [2, 2]

x = 0 f (0) = 0 (0, 0)

f (x) = 0 x y = 0 (2, 0) (0, 0) (2, 0)

f

f

(x) = 2(x 2 2)

(x) =

4 x 2 2x(x 2 6)

(4 x 2 ) 3

f (x) = 0

x = 2 x = 2.

f ( 2) < 0 x = 2 f ( 2) >

0 x = 2 f (x)

[2, 2) ( 2, 2) ( 2, 2] f (x) 1,9 0 1,9

x [2, 2) f (x) < 0 f (x)

x ( 2, 2) f (x) > 0 f (x)

x ( 2, 2] f (x) < 0 f (x)

x = 0 f (x) x (2, 0) f (x) > 0 f (x) x (0, 2) f (x) < 0 f (x) x = 0 (0, 0)

x (4 − x 2 ) 1/2 2 1.5 1 0.5 0 −0.5 −1 −1.5
x (4 − x 2 ) 1/2
2
1.5
1
0.5
0
−0.5
−1
−1.5
−2
−2
−1.5
−1
−0.5
0
0.5
1
1.5
2
x

(2, 0) (2, 0)

0

−0.05

−0.1

−0.15

−0.2

−0.25

−0.3

−0.35

−0.4

x (4 − x 2 ) 1/2
x (4 − x 2 ) 1/2
−0.2 −0.25 −0.3 −0.35 −0.4 x (4 − x 2 ) 1/2 −2.008 −2.006 −2.004 −2.002

−2.008 −2.006 −2.004 −2.002

−2

−1.998 −1.996 −1.994 −1.992 −1.99

x